(untitled) (Alternautas, 2022)
“Brazil is back on the world stage” – this was the main message Lula delivered as honorary guest at the UN Climate Summit in Egypt, less than a month after beating Bolsonaro in the runoff of Brazil’s presidential elections with a narrow margin of 50.9% against 49.1%. Lula’s high-strung victory in a divided country has attracted global media and political attention, reflecting not only concerns about the fate of Brazilian democracy after a long cycle of authoritarianism (2016-2022), but of how the election could point to a change in the correlation of forces in a number of consequential themes that resonate on the international agenda: the urgency of environmental protection and regulation, the resumption of the South American integration process, the possibility of a more assertive BRICS coalition pushing for a transition in economic development policies, the attention to social inclusion, the need to reverse neoliberal reforms related to labour market and public spending mechanisms, the hopes of re-organising international left-wing solidarity, among others.